Comportamentos, térmico e mecânico, de compósitos de polipropileno e resíduo da hidrólise enzimática do bagaço de cana de açúcar - Oliveira, Rodrigo Andrade de [UNESP] (2014)
In this work is presented the production via kinetic term mixing and injection of polypropylene composites reinforced with both delignified and enzymatic hydrolyzed residue bagasse from sugarcane, at different concentrations (5%, 10% and 25%, (w / w)). Polymeric composites were characterized via mechanical tests of tensile, three points bending flexural and Izod impact. Furthermore, tests for determining the thermal properties were done (melting and crystallization temperatures by differential scanning calorimetry (DSC), temperature of degradation by thermogravimetric analysis (TGA) and glass transition temperature (Tg) by dynamic mechanical (DMA)). Analyses of Fourier transform infra-red spectroscopy (FTIR) and scanning electron microscopy (SEM) were done for the composites. After this, the polymeric composites were subjected to conditioning in the ultraviolet radiation camera (UV) to evaluate the wheathering influence on the mechanical and thermal properties. FTIR results showed the presence of interface between the matrix (PP) and lignocellulosic materials. DSC and TGA analyzes showed that the melting temperatures of crystallization and thermal degradation are within the values reported on literature, indicating that the kinetic term processing and injection did not affect the thermal properties of the composites. Tg was not affected by the introduction of reinforcement agents. However, when the composites were subjected to exposure to UV radiation, the values of Tg of the composites were increased. The mechanical properties evaluated in this study did not change or significant gains with the introduction of reinforcements in composites, however, when exposed to UV radiation for conditioning such properties suffered less significant reductions when compared with the samples of the polypropylene